The Krümmel (Germany) Childhood Leukaemia Cluster: a review and update. (15th November 2017) - Grosche, B; Kaatsch, P; Heinzow, B; Wichmann, H-E
Abstract: The debate surrounding possible adverse health effects from the civil use of nuclear power under normal operating conditions has been on-going since its introduction. It was particularly intensified by the detection of three leukaemia clusters near nuclear installations, i.e. near the reprocessing plants in Sellafield and Dounreay, UK, and near the Krümmel nuclear power plant, Germany, the last of which commenced between 1990 and 1991 and was first described in 1992; it continued until 2003, and an elevated risk up to 2005 has been reported in the literature. A number of expert commissions and working groups were set up by the governments of the German federal states of Lower Saxony and Schleswig-Holstein to investigate the possible causes of the cluster. An overview of the many risk factors that were investigated as a possible explanation of the Krümmel cluster is given here, focussing on radiation, but also including other risk factors. Further, results from related epidemiological and cytogenetic studies are described. In summary, the cause of the occurrence of the Krümmel cluster has to be considered as unknown. Further research on the causes of childhood leukaemia is needed, focussing on epigenetics and on gene-environment interaction. An update of the leukaemia incidence around the Krümmel site shows that the incidence rates are now comparable to the average rate in Germany.